2014
DOI: 10.1371/journal.pone.0097429
|View full text |Cite
|
Sign up to set email alerts
|

Two Speed Factors of Visual Recognition Independently Correlated with Fluid Intelligence

Abstract: Growing evidence indicates a moderate but significant relationship between processing speed in visuo-cognitive tasks and general intelligence. On the other hand, findings from neuroscience proposed that the primate visual system consists of two major pathways, the ventral pathway for objects recognition and the dorsal pathway for spatial processing and attentive analysis. Previous studies seeking for visuo-cognitive factors of human intelligence indicated a significant correlation between fluid intelligence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This method deals with outliers with higher precision and resistance and is less affected by the sample size than the other more common methods (for example, those discarding trials with saccade performance below and above 2.5 SD; see Carling, 2000). 1 Furthermore, this method is more and more used by researchers from different fields (e.g., Alahyane et al, 2016;Kulesz, Tian, Juranek, Fletcher, & Francis, 2015;Lemoine-Lardennois et al, 2016;Letham & Raij, 2011;Pernet et al, 2015;Tachibana, Namba, & Noguchi, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This method deals with outliers with higher precision and resistance and is less affected by the sample size than the other more common methods (for example, those discarding trials with saccade performance below and above 2.5 SD; see Carling, 2000). 1 Furthermore, this method is more and more used by researchers from different fields (e.g., Alahyane et al, 2016;Kulesz, Tian, Juranek, Fletcher, & Francis, 2015;Lemoine-Lardennois et al, 2016;Letham & Raij, 2011;Pernet et al, 2015;Tachibana, Namba, & Noguchi, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Staufer et al (2012) found that a collection of temporal processing task were best described by a hierarchical model with modality specific auditory and visual factors and a second-order general factor. However other researchers have found a more complex, non-unitary relationship between measures of information processing speed and intelligence (Danthiir et al, 2012; Tachibana et al, 2014). …”
Section: Speed Of Information Processingmentioning
confidence: 94%
“…Following Session 1, participants were stratified into either a 3D group ( n = 21), a 2D group ( n = 21), or a cadaver group ( n = 22) based on controlling for Vz, sex, and academic year to ensure that all groups were demographically equal and were of equal spatial abilities. There is some evidence to suggest that fluid intelligence is associated with mental rotation ability (Ozer, 1987; Tachibana et al, 2014; Varriale et al, 2018); this potential relationship was controlled for through stratification and equal distribution of participants by MRT score in all three groups.…”
Section: Methodsmentioning
confidence: 99%